Identification of MORF4L1 as an endogenous substrate of CRBN and its potential role as a therapeutic target in cancer - Luyao Zhang; Shunfang Liu; Jingliang He; Zhongke Hu; Lan Zhu; Hongyi Huang; Qi Gao; Dan Wang; Lu Chen; Xingyu Zhang; Ruotong Liu; Jiayun Wang; et al. (Scientific Reports)
Abstract The ubiquitin-proteasome system (UPS) is essential for cellular homeostasis, regulating the degradation of proteins involved in key processes such as cell cycle, apoptosis, and DNA repair. Dysregulation of the UPS is implicated in hepatocellular carcinoma (HCC), contributing to tumor progression and therapeutic resistance. The cereblon (CRBN) E3 ubiquitin ligase complex is a crucial component of the UPS, particularly in modulating protein degradation in response to small-molecule modulators like thalidomide. However, the endogenous substrates of CRBN in solid tumors like HCC remain poorly characterized. Here, we identify MORF4L1, a member of the MRG family involved in chromatin remodeling and DNA damage response, as a substrate of CRBN. Using proteomic analysis, co-immunoprecipitation, and structural modeling, we demonstrate that CRBN promotes MORF4L1 degradation under physiological conditions, which is further enhanced by the modulator CC-885. Importantly, MORF4L1 is upregulated in multiple cancers, including HCC, suggesting a broader role in tumorigenesis. Our findings reveal MORF4L1 as a physiological CRBN substrate and highlight the therapeutic potential of targeting CRBN substrates in cancer.